Мефодий Буслаев. Стеклянный страж: повесть / Дмитрий Емец - Емец Дмитрий Александрович (Мефодий Буслаев, 2009)
Экземпляры: ф. 4 (20091028) / Инвентарный номер: 95449 / Цена: 171.50 / Авт.знак: Е 60 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6